Comparison of DPPH Free Radical Scavenging, Ferric Reducing Antioxidant Power (FRAP), and Total Phenolic Content of Two Meriania Species (Melastomataceae) - Valverde Malaver, Claudia Lorena; Colmenares Dulcey, Ana Julia; Isaza Martínez, José Hipólito (Revista de Ciencias, 2015)
Searching for new antioxidants used in pharmaceuticals, cosmetics or agrochemicals have increased today. Many phenolic compounds have been reported as promising for this goal. Melastomataceae is rich in these compounds. Consequently, in this research the antioxidant power for Meriania nobilis and M. hernandoi (Melastomataceae) was compared.